STUDI TENTANG IMPLEMENTASI MEDIA PEMBELAJARAN E-LEARNING SEBAGAI PENDUKUNG PERKULIAHAN PADA PROGRAM STUDI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU TAHUN 2019 - Lara Sari Wanti; Ahmad Eddison; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to find out how e-learning implementation is used by lecturers in supporting lectures for students in Pancasila education Program and citizenship Faculty of Teaching and Educational sciences Riau University year 2019. The subject of this study is the student education Program of Pancasila and citizenship. The samples in this researcher were based on Proportional Sampling technique with a subject number of 25% from 222 students. The data collection techniques used are observation techniques, polls, interviews and documentation. In analyzing the researcher's data using quantitative descriptive method. The results of the research conducted, then it can be concluded that the overall data on the planning needs of E-Learning based on Pancasila education Program and citizenship Faculty of Teaching and Education sciences University of Riau, 2019 that implemented at 68% and facilities and facility of Online learning technology in Pancasila education Program and citizenship Faculty of teacher training and education in Riau University year 2019 Implemented at 77%.Key Words: Implementation, E-Learning, Pancasila Education And Citizenship